Refleksi terhadap Tujuan Hukum dengan Delik Aduan dalam Pasal 284 KUHP tentang Perzinahan Perspektif Maqashid Syari’ah - Moh. Aprizal Ardianto; Syamsuri Syamsuri; Muhammad Waliyuddin Yusuf (AHKAM, 2025)
The formation of law aims to maintain order and social protection while preserving a sense of justice, including within the sphere of societal morality. Article 284 of the Indonesian Criminal Code, which regulates the criminal act of adultery, is intended as a legal instrument to safeguard social order; however, the complaint-based (delik aduan) mechanism inherent in this provision often generates new social conflicts and is considered less compatible with efforts to uphold morality in society. This article seeks to reflect on the compatibility of the regulation of adultery in Article 284 of the Criminal Code with the principles of maqasid syari’ah. The study employs a normative juridical method, taking the Indonesian Criminal Code as the primary legal source, supported by secondary legal sources in the form of literature reviews, doctrines, legal theories, and expert opinions. The findings indicate that Article 284 constitutes an absolute complaint-based offense which, in practice, has the potential to hinder the attainment of legal objectives, reduce the effectiveness of law enforcement, and open space for social impunity, thereby not fully reflecting the protection of the values of maqasid syari’ah. These results point to a tension between the construction of the complaint-based offense in Article 284 of the Criminal Code and the moral protection objectives that constitute the primary orientation of maqasid syari’ah, thus requiring a critical reading of the role of this article as an instrument for guaranteeing social order and justice.